PENEGAKAN HUKUM HAK CIPTA TERHADAP PRAKTIK PEMBAJAKAN FILM BESERTA SANKSI DAN DAMPAK YANG TERJADI - Wibisono, Rayhan Satrio; Rani Apriani (Fakultas Hukum Universitas Islam Syekh Yusuf, 2024)
In the preparation of this article, which aims to discuss the problem of violating the law and criminal sanctions against copyright infringement in piracy and distribution of pirated films. Copyright (Copyright) is the right of the creator that appears by itself based on a declarative principle after the realization of the Work in a tangible form without restrictions according to laws and regulations. The results in this article aim to find out how copyright law enforces the practice of film piracy due to the rampant piracy and distribution of pirated films and what sanctions will be received by the perpetrators of film piracy practices. The perpetrators of piracy must receive applicable sanctions in accordance with the regulations regulated in Law Number 28 of 2014 concerning Copyright and the Indonesian people need to receive education about the forms of sanctions that apply to copyright violators because the practice of film piracy can violate the Act Copyright Law whose laws and sanctions have been regulated therein. Keyword : Copyright; Film; Piracy; and Â Sanctions.